PENYELESAIAN SENGKETA DAN AKIBAT HUKUM HAK GUNA USAHA UNTUK PERKEBUNAN - Yunantha, Rachmat; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
Hak Guna Usaha is the right to cultivate land directly controlled by the State, within a certain period of time, for agricultural, fishery or livestock enterprises. Business Use Rights can be owned by Indonesian citizens and legal entities that have been established in Indonesia according to Indonesian law and are domiciled in Indonesia. This research is normative juridical research. The type of approach in the writing method, the author uses a statutory approach, comparative approach, historical approach and conceptual approach. The data obtained in this study were analysed using a qualitative method, namely a data analysis method that classifies and selects the data obtained. The results of the analysis are presented descriptively so that a descriptive-qualitative description of the research results is obtained and described in the form of sentences which are then organized and systematic. For example, the case of the Constitutional Court Decision Number 859/Pid.Sus/2017/PN.Kpn. that the defendant Ari Ismanto Bin Tukirin in January 2016 to October 2017 took place on PTPN XII Kebun Pancursari Afdeling Sumberkerto/Sumbermanggis (SK/SM) Sumbermanggis Hamlet, Tegalrejo Village, Sumbermanjing Wetan District, Malang Regency. Dispute settlement between PT Perkebunan Nusantara XII and Tegalrejo Village community by conducting 2 (two) efforts, namely through litigation and non-litigation. The legal consequences after the dispute between PT Perkebunan Nusantara XII and Tegalrejo Village community is that the panel of judges with several considerations determined that the actions committed by one of Tegalrejo Village residents as the defendant was declared to have violated the law.Keywords: Cultivation Rights, Plantation, Dispute Resolution.